Relation between Antibiotic Susceptibility and Ultrastructure of Staphylococcus aureus Biofilms on Surgical Suture - Wells, Carol L. (Mary Ann Liebert, Inc., 2011)
BACKGROUND: Infectious biofilms are recalcitrant to antimicrobial therapy, but the mechanism(s) responsible for the greater resistance are unclear. Experiments were designed to clarify the association between antibiotic resistance and biofilm ultrastructure. METHODS: Staphylococcus aureus was cultivated for 24 h on silk suture, where robust biofilms formed. Initial experiments compared the susceptibilities of planktonic (free-living) cells and mechanically dispersed biofilm cells to ampicillin, oxacillin, and vancomycin. Antibiotics in bactericidal concentrations were then incubated overnight with 24-h biofilms, and subsequent assays determined the viability of cells in mechanically dispersed biofilms, biofilm metabolic capacity and biomass, and biofilm ultrastructure (scanning electron microscopy). RESULTS: Planktonic and biofilm cells had similar intrinsic antibiotic susceptibility. Nonetheless, a stable population of bacteria remained viable after biofilms were incubated with inhibitory drug concentrations, although biofilm metabolic capacity often was not detected, and biomass generally was reduced. Electron microscopy revealed that control (no drug) biofilms consisted primarily of bacterial clusters amid fibrillar elements. Antibiotic-treated biofilms had some staphylococci with smooth cells walls similar to planktonic cells, but other cocci were encased in extracellular material. This material was more abundant in antibiotic-treated than in control biofilms. CONCLUSIONS: In the presence of high antibiotic concentrations, dense extracellular material may inhibit interaction of antibiotics with their bacterial targets.